Rare lung disease II: pulmonary alveolar proteinosis. - Juvet, S; Hwang, D; Waddell, T; Downey, G (2008)
The present article is the second in a series on rare lung diseases. It focuses on pulmonary alveolar proteinosis (PAP), a disorder in which lipoproteinaceous material accumulates in the alveolar space. PAP was first described in 1958, and for many years the nature of the material accumulating in the lungs was unknown. Major insights into PAP have been made in the past decade, and these have led to the notion that PAP is an autoimmume disorder in which autoantibodies interfere with signalling through the granulocyte-macrophage colony-stimulating factor receptor, leading to macrophage and neutrophil dysfunction. This has spurred new therapeutic approaches to this disorder. The discussion of PAP will begin with a case report, then will highlight the classification of PAP and review recent insights into the pathogenesis of PAP. The approach to therapy and the prognosis of PAP will also be discussed.